The Analytical Thinking Skill of Grade XI Students of SMA Negeri 15 Semarang - Muhartati, Dwi; Isnaeni, Wiwi; Ridlo, Saiful (Journal of Biology Education, 2019)
This research aims to study the development of students’ analytical thinking skill during animal tissue learning. The other aim is to identify the obstacles experienced by the teacher in developing the students’ analytical thinking skill during learning process. The study used case study design. The study was held on odd semester of academic year 2017/2018. The samples were XI IPA5, XI IPA6, dan XI IPA7. The datas in this research are the data of learning implementation, students’ analytical thinking skill, and the teacher’s obstacles during the learning. The data of learning implementation was obtained from observation sheets. The data of students’ analytical thinking skill was obtained from observation and test. The data of challenge which was experienced by teacher and students’ response were obtained from teacher and students’ questionnaire. The data of learning implementation is analyzed by measuring the percentage of learning process implementation. Based on that percentage, the implementation of learning held by teacher can be categorized into very well, well, and dissatisfactory. The data of analytical thinking skill was analyzed by calculate the score of analytical thinking skill test. Based on that score, students were grouped into 3 categories; high, medium, and low. The data of teacher and student responses were analyzed by calculating the score percentage of teacher and students questionaires. The result of study showed that students’ analytical thinking skill developed well through lecture method (67%), and it developed very well through discussion method (89%). Most of the students (68%) had medium analytical thinking. The teacher challenged the development of indicator of analytical thinking skill in evaluating opinion, and collecting and assessing information. According to the students, their analytical thinking skill developed well during the learning.